Effect of Attending Pregnant Mothers Conference on Birth Preparedness and Complication Readiness Practice among Recently Delivered Women in Rural Libo Kemkem District, North West, Ethiopia: A Community-Based Comparative Cross-Sectional Study - Melash Belachew Asresie; Dereje Berhanu Abitew; Habtamu Wondiye Bekele; Tadesse Dagget Tesfaye (Advances in Public Health)
Background. Birth preparedness and complication readiness strategies aimed to promote the timely utilization of skilled maternal health care. Pregnant mother conference is viewed as one of the needed interventions to reduce delays, by promoting obstetric danger sign awareness, family support, and decision-making power on a choice of place of delivery and the use of maternal health service. Objective. To compare the effect of attending a pregnant mother conference on birth preparedness and complication readiness practice among recently delivered women. Method. A community-based comparative cross-sectional study was conducted from February 15 to March 26, 2017, among mothers who gave birth in the past 12 months. Multistage simple random sampling method was implemented and 896 participants were contacted through a face-to-face interview. Descriptive, binary, and multiple logistic regression analysis was done. Results. Well-preparedness for birth and its complication among women who attended and did not attend the pregnant mother conference were 38.9% and 25.7%, respectively. Among the mothers who did not attend the conference, those who had four or more antenatal care visits (AOR=6.8, 95%CI 1.6, 29.8) and knew two or more danger signs of pregnancy (AOR=4.7, 95%CI:1.4, 15.6) were more likely being well-prepared for birth and its complication readiness, whereas among mothers who attended the conference, those who knew two or more danger signs of pregnancy (AOR=2.1, 95%CI:1.1, 4.3), those who had discussion with partners/families about place of delivery (AOR=11.4, 95%CI:3.1, 42.2), those who had previous delivery at health facility (AOR=2.4, 95%CI:1.2, 4.8), women who lived within one-hour walk to the nearest health facility (AOR=3.6, 95%CI:1.9, 6.9), and age of women within 19-34 years (AOR=6.8, 95%CI:1.7, 26.6) were significantly associated with birth preparedness and its complication readiness. Conclusion. Birth preparedness and complication readiness practice were higher among pregnant mother conference attendant women as compared to nonattendants. The health facility has to ensure encouraging women to participate in pregnant mother conference, promoting the utilization of antenatal care service, and counselling on obstetric danger sign. Moreover, the concerned bodies should promote interventions targeting the predisposing and reinforcing behavioral factors affecting the practice of birth preparedness and its complication readiness.